From cell death to neurological disease: Unraveling the role of copper - Qiqi Gao; Yu Chen; Wei Hu; Tong Lou; Yu Fang; Zhenlang Lin; Wei Lin (Neurobiology of Disease, 2025)
Copper, a transition metal, plays a crucial role in various physiological processes within the human body. Its homeostasis is vital for maintaining normal cellular function and facilitating optimal performance of the nervous system. To regulate this homeostasis, cells employ sophisticated regulatory mechanisms that govern intracellular copper levels, allowing an adequate supply of copper ions to participate in essential biological functions such as mitochondrial energy production, antioxidant defense, and extracellular matrix stability. Cuproptosis, which was first systematically described in 2022 as a novel form of programmed cell death, involves molecular mechanisms characterized by oxidative stress activation, inhibition of the ubiquitin-proteasome system, and aggregation of lipoacylated proteins. This cascade can compromise mitochondrial function and ultimately result in cell death. In this review, we summarize current knowledge regarding copper metabolism, cuproptosis mechanism, copper-associated cell death, and copper-associated neurological diseases. Importantly, we sought to enhance the current understanding of copper's influence on cellular processes and disease states while advancing clinical approaches for treating these conditions.